Odpowiedzi

2009-10-10T17:56:07+02:00
A) 2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2 /:(-2)
x=1

b) 4-2(5-x)=x-4(x-1)
4-10+2x=x²-x-4x+4
-x²+x+4x+2x+4-10-4=0
-x²+7x-10=0
a=-1 b=7 c=-10
delta=7²-4*(-1)*(-10)
delta=49-40
delta=9
√delta=√9=3
x₁=(-7-3)/-2
x₁=5
x₂=(-7+3)/-2
x₂=2

c) 7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4-7+4
-2x=-6 /:(-2)
x=3

d) x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4
2009-10-10T18:14:26+02:00
Po co tak kombinować? wszystko jest prościutkie :)

a) 2x-(1-4x)=2+(8x-5)
2x-1-4x=2+8x-5
2x-4x-8x=2+1-5
-10x=-2 |:(-10)
x=0,2

b) 4-2(5-x)=x-4(x-1)
4-10+2x=x-4x+4
2x+4x-x=4-4+10
5x=10|:5
x=2

c) 7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4+5-7
-2x=-6|:(-2)
x=3

d) x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4

Sprawdzałem wszystko 2 razy^^


Najlepsza Odpowiedź!
2009-10-10T18:33:14+02:00
Rozwiąż równania:
a) 2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
-2x=-2
x=1

b) 4-2(5-x)=x-4(x-1)
4-10+2x=x-4x+4
5x=10
x=2

c) 7-3x-4=x+1-2x-4
-2x =-6
x=3

d) x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x=4